2013
DOI: 10.1016/j.apsusc.2012.11.085
|View full text |Cite
|
Sign up to set email alerts
|

Wetting behaviour of femtosecond laser textured Ti–6Al–4V surfaces

Abstract: Abstract:The aim of the present work was to investigate the wetting behaviour of biomedical grade Ti-6Al-4V alloy surfaces textured by a femtosecond laser treatment. The material was treated in ambient atmosphere using an Yb: KYW chirped-pulse-regenerative amplification laser with a wavelength of 1030 nm and a pulse duration of 500 fs. Four main types of surface textures were obtained depending on the processing parameters and laser treatment method. These textures consist of: (1) nanoscale laser-induced perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(103 citation statements)
references
References 43 publications
6
96
1
Order By: Relevance
“…The contact angle decreases from 60 o for as received sample to 55 o for dimple textured and 50 o for liner textured surface (parallel to grooves direction) and 45 o (perpendicular to grooves direction) degree. Cunha et al [34] showed the wetting behavior is anisotropic, reflecting the anisotropy of the surface textures.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle decreases from 60 o for as received sample to 55 o for dimple textured and 50 o for liner textured surface (parallel to grooves direction) and 45 o (perpendicular to grooves direction) degree. Cunha et al [34] showed the wetting behavior is anisotropic, reflecting the anisotropy of the surface textures.…”
Section: Resultsmentioning
confidence: 99%
“…In order to solve these problems, femtosecond laser micro-nano machining has emerged as an effective technique to create dual scaled surfaces with nano-and micro-structures [17], [18], [19]. Chloroalkylsilane and fluoroalkylsilane coatings are frequently used to greatly decrease the surface energies of the laser machined surfaces and to obtain the highest contact angles [20].…”
Section: Introductionmentioning
confidence: 99%
“…Femtosecond laser treatments allow to achieve various surface textures on such biomedical implants. These textures consist of nanoscale laser-induced periodic surface structures (LIPSS), nano-pillars, micro porous columns and complex textures which are nowadays being adopted for implants due to different wettability characteristics [35]. The increase in fluence also alter the microstructure and wear resistance of implants positively in terms of surface grain size and hardness [36].…”
Section: Laser Beam Milling Of Titanium Alloysmentioning
confidence: 99%